INSTRUMENTAL METHODS OF MONITORING CITY LANDS - Nesterenko, S.; Radzinska, Y.; Kondratyuk, І.; Khalikov, S. (Municipal economy of cities. Series: «Economy science», 2023)
Urban land monitoring is an important component of effective land management. Instrumental monitoring of urban land is necessary for the collection and analysis of data on land plots, which allows for effective management of urban land, planning of city development, and environmental safety. One of the main tools for city land monitoring is geoinformation systems. Remote sensing of the Earth, navigation and positioning systems, land resource databases are another tool for monitoring urban land. These databases are the basis for monitoring urban land and are used to make decisions on planning and management of land resources. For the effective use of instrumental support for city land monitoring, appropriate qualifications of specialists and engineers who will be engaged in data collection and analysis are required. It is also important to have sufficient resources and funding for tool development and implementation. The purpose of the article is to research modern approaches, methods and principles of instrumental monitoring of urban lands. The study presents methods and technologies of instrumental monitoring of urban lands. The areas of instrumental provision for monitoring the land of cities have been analyzed. Monitoring urban land is a very important task that has a significant impact on our planet and our shared future. To do this, it is important to have access to accurate and objective statistical data that will allow for proper planning and control of the use of land resources in cities. According to the research results, it was found that the instrumental methods of city monitoring are an important tool for ensuring the sustainable development of cities and improving the quality of life of residents. They allow collecting accurate and objective data on the state of urban areas and using them for planning the development of cities and managing urban infrastructure. It has been proven that the instrumental methods of city monitoring should be used in combination with other methods and approaches to ensure a comprehensive and multifaceted analysis of the state of cities and their development.